The role of solar ultraviolet irradiation in zoster. - Zak-Prelich, M. (Cambridge University Press, 2002)
Ultraviolet radiation (UVR) suppresses many aspects of cell-mediated immunity but it is uncertain whether solar UV exposure alters resistance to human infectious diseases. Varicella-zoster virus (VZV) causes varicella (chickenpox) and can reactivate from latency to cause zoster (shingles). The monthly incidence of chickenpox and zoster in a defined Polish population over 2 years was recorded and ground level solar UV was measured daily. There was a significant seasonality of UVR. Evidence of seasonal variation was found for all zoster cases and for zoster in males, with the lowest number of cases in the winter. The number of zoster cases with lesions occurring on exposed body sites (the face) demonstrated highly significant seasonality with a peak in July/August. Seasonal models for UVR and zoster cases showed similar temporal patterns. By contrast, for varicella, the maximum number of cases was found in March and the minimum in August/September, probably explained by the respiratory spread of VZV. It is tempting to speculate that the increase in solar UVR in the summer could induce suppression of cellular immunity, thus contributing to the corresponding rise in the incidence of zoster.